Pelatihan Daring Aplikasi Media Sosial dalam Pemasaran Produk Kerajinan Bambu di Selaawi, Garut, Jawa Barat - Santi Susanti; Rachmaniar Rachmaniar; Iwan Koswara (Universitas Mathla'ul Anwar Banten, 2020)
ONLINE TRAINING OF SOCIAL MEDIA APPLICATION FOR MARKETING BAMBOO CRAFT PRODUCT IN SELAAWI, GARUT, WEST JAVA. The distribution of goods and services needs marketing to reach the potential customers. The development of internet technology expand the marketing of goods and services from traditional to online market. The bamboo artisans of Selaawi Subdistrict, Garut Regency, realized that it was necessary to market their products online to increase the market share of their craft products, which are currently distributed offline. The Community Service (PPM) Team of Fikom Unpad conducted